Internalisasi Nilai-Nilai Multikultural Dalam Mata Pelajaran Pendidikan Agama Islam - Wahidah, Evita Yuliatul; Marlina, Leny (STAI Al-Musaddadiyah Garut, 2025)
This research will explain the problems faced by this nation, namely the lack of mutual respect and an open attitude in accepting every difference both in the context of social relations, human rights and religious life. The importance of internalising multicultural values in order to create a generation that is inclusive and appreciates diversity so that schools can provide learning that is oriented towards students' awareness of the importance of having an attitude of tolerance. This research aims to describe in general about the development of internalisation of multicultural values, strategies and supporting and inhibiting factors in learning Islamic Religious Education (Study at SD Daya Susila Garut). This research uses a qualitative approach, with descriptive analytical research methods. The data were collected through interviews, observations, and documentation. Data analysis used Miles and Hubberman's theory of data reduction, data presentation and conclusion. Based on the results of the research, the internalised multicultural values are reflected in the mutual respect, tolerance, and solidarity shown by the students in their daily lives. The strategy is to create an inclusive educational environment, respect religious pluralism, promote good social and ethical values, and provide positive examples to students through real actions. Supporting and inhibiting factors include the support of educational institutions, diversity in the school environment, internal factors of teachers and students, and PAI learning materials.Keywords: value internalisation, multicultural, PAI subject